Comparison of the chemical composition of PM10 and PM2.5 particles collected in urban environments and volcanic areas of metropolitan Costa Rica - Herrera, Jorge (2014)
PM10 and PM2,5 were sampled simultaneously in urban and volcanic environments in the Metropolitan Area of Costa Rica from October to November 2012. Higher mass concentrations (42-29 μgm-3) of PM10 and PM2,5 were found at industrial and commercial areas with high traffic flow (La Uruca, Heredia and Belen) compared with those found in the volcanic areas. The daily concentrations of PM10 and PM2,5 obtained in the Poas Volcano ranged from 3 -14 μgm-3 and 2-11 μgm-3, respectively. However the acidity of the collected particles in the Poas volcano was higher than those sampled in urban environments probably due to a lower occurrence rate of neutralization. The contribution of secondary ions was more important to the volcanic PM10 composition (around 40%), unlike the PM10 collected in urban areas.